Regulation of Nitrogen Fixation in Bradyrhizobium sp. Strain DOA9 Involves Two Distinct NifA Regulatory Proteins That Are Functionally Redundant During Symbiosis but Not During Free-Living Growth - Wongdee, Jenjira; Boonkerd, Nantakorn; Teaumroong, Neung; Tittabutr, Panlada; Giraud, Eric (Frontiers in Microbiology, 2018)
The Bradyrhizobium sp. DOA9 strain displays the unusual properties to have a symbiotic plasmid and to fix nitrogen during both free-living and symbiotic growth. Sequence genome analysis shows that on each replicon, this strain contains the structural genes of dinitrogenase (nifDK) and the nifA regulatory gene. It was previously shown that both nifDK clusters are differentially expressed depending on lifestyle, suggesting different mechanisms of regulation. In this study, we examined the functional regulatory role of the two nifA genes found on the plasmid (nifAp) and chromosome (nifAc) that encode proteins with a moderate level of identity (55%) and different structural architectures. Using gusA reporter strains, we showed that both nifA genes were expressed during both the free-living and symbiotic growth stages. During symbiosis with Aeschynomene americana, mutants in only one nifA gene were not altered in their symbiotic properties, while a double nifA mutant was drastically impaired in nitrogen fixation, indicating that the two NifA proteins are functionally redundant during this culture condition. In contrast, under in vitro conditions, the nifAc mutant was unable to fix nitrogen, and no effect of the nifAp mutation was detected, indicating that NifAc is essential to activate nif genes during free-living growth. In accordance, the nitrogenase fixation deficiency of this mutant could be restored by the introduction of nifAc but not by nifAp or by two chimeric nifA genes encoding hybrid proteins with the N-terminus part of NifAc and the C-terminus of NifAp. Furthermore, transcriptional analysis by RT-qPCR of the WT and two nifA mutant backgrounds showed that NifAc and NifAp activated the expression of both chromosome and plasmid structural nifDK genes during symbiosis, while only NifAc activated the expression of nifDKc during free-living conditions. In summary, this study provides a better overview of the complex mechanisms of regulation of the nitrogenase genes in the DOA9 strain that involve two distinct NifA proteins, which are exchangeable during symbiosis for the activation of nif genes but not during free-living growth where NifAc is essential for the activation of nifDKc.